Unlocking the therapeutic potential of Pelargonium sidoides natural extract: A scoping review - Reina, Bárbara Donadon [UNESP]; Malheiros, Samuel Santana; Vieira, Sâmmea Martins [UNESP]; Ferreira de Andrade, Paula; Dovigo, Lívia Nordi [UNESP] (Elsevier, 2024)
Pelargonium sidoides DC. (Geraniaceae) is a widely recognized medicinal plant whose natural extract exhibits therapeutic effects through a multi-target approach. Existing literature encompasses investigations of antimicrobial and cellular effects, including clinical trials. A comprehensive review is required to summary the substantial number of published investigations and to grasp the potentialities of this extract. The aim of this scoping review was to provide an overview of the antimicrobial, antiadhesive, immunomodulatory, and respiratory effects of the P. sidoides extract, along with a discussion of its mechanism of action, clinical safety, potential repurposing uses, and areas requiring further investigation. A systematic search of Medline (PubMED) and Scopus databases was conducted using the terms: EPs7630, Pelargonium, Pelargonium sidoides. The search process was finished on 5th, June 2024. Two researchers screened titles and abstracts according to the eligibility criteria, which included in vitro, in vivo, randomized, and non-randomized clinical trials. Out of 4367 publications identified, 134 studies were included in this review. A structured form was applied for data extraction. PRISMA-ScR was used to guide reporting of this review. Most of the studies were conducted in vitro, followed by human studies and animal models. The findings demonstrated a strong and broad-spectrum antimicrobial and antiadhesive effect against various bacterial, fungi, and virus species. Additionally, a strong immunomodulatory effect was observed, including the induction of pro-inflammatory cytokines during infection, and modulation of other immune response components. The effects on the respiratory system have been extensively examined, showing remarkable clinical efficacy against both bacterial and viral infections with no significant cytotoxicity or adverse effects. Furthermore, recent research showed an anti-COVID effect by direct antiviral and immunomodulation mechanisms. Nonetheless, the establishment of a concentration protocol to further studies is still challenging due to variations in extract origin, composition and extraction methods. In this sense, the use of a commercial extract such as EPs® 7630 is of great value to facilitate the standardization of the tested protocols. The noteworthy anti-infective potential of P. sidoides extract lies in its multifaceted mechanism of action, which encompasses direct microbicidal effects and modulation of the immune response. These unique properties establish P. sidoides extract as a promising alternative in the war against a wide range of infectious diseases.
Keywords: Anti-infective agents; COVID-19; EPs 7630; Immunomodulation; Pelargonium sidoides; Plant extracts; Umckaloabo